Effects of Nitrogen Application on Growth and Ethanol Yield of Sweet Sorghum [Sorghum bicolor (L.) Moench] Varieties - Oluwatoyin Olugbemi; Yekeen Abiola Ababyomi (Advances in Agriculture)
A study was carried out in two locations, Ilorin (8° 29′ N; 4° 35′ E; about 310 m asl) and Ejiba (8° 17′ N; 5° 39′ E; about 246 m asl), at the Southern Guinea Savannah agroecological zone of Nigeria to assess the effect of nitrogen fertilizer on the growth and ethanol yield of four sweet sorghum varieties (NTJ-2, 64 DTN, SW Makarfi 2006, and SW Dansadau 2007). Five N fertilizer levels (0, 40, 80, 120, and 160 kg ha−1) were used in a 4 × 5 factorial experiment, laid out in split-plots arrangement. The application of nitrogen fertilizer was shown to enhance the growth of sweet sorghum as observed in the plant height, LAI, CGR, and other growth indices. Nitrogen fertilizer application also enhanced the ethanol yield of the crop, as variations in growth parameters and ethanol yield were observed among the four varieties studied. The variety SW Dansadau 2007 was observed as the most promising in terms of growth and ethanol yield, and the application of 120 kg N ha−1 resulted in the best ethanol yield at the study area.